Evaluation of pyrrolizidine alkaloid-induced genotoxicity using metabolically competent TK6 cell lines. (November 2020) - Li, Xilin; He, Xiaobo; Chen, Si; Guo, Xiaoqing; Bryant, Matthew S.; Guo, Lei; Manjanatha, Mugimane G.; Zhou, Tong; Witt, Kristine L.; Mei, Nan
Abstract: Pyrrolizidine alkaloid (PA)-containing plants are among the most common poisonous plants affecting humans, livestock, and wildlife worldwide. A large number of PAs are known to induce genetic damage after metabolic activation. In the present study, using a battery of fourteen newly developed TK6 cell lines, each expressing a single human cytochrome P450 (CYP1A1, 1A2, 1B1, 2A6, 2B6, 2C8, 2C18, 2C9, 2C19, 2D6, 2E1, 3A4, 3A5, and 3A7), we identified specific CYPs responsible for bioactivating three PAs – lasiocarpine, riddelliine, and senkirkine. Among the fourteen cell lines, cells expressing CYP3A4 showed significant increases in PA-induced cytotoxicity, evidenced by decreased ATP production and cell viability, and increased caspase 3/7 activities. LC-MS/MS analysis revealed the formation of 1-hydroxymethyl-7-hydroxy-6, 7-dihydropyrrolizine (DHP), the main reactive metabolite of PAs, in CYP3A4-expressing TK6 cells. DHP was also detected in CYP3A5- and 3A7-expressing cells after PA exposure, but to a much lesser extent. Subsequently, using a high-throughput micronucleus assay, we demonstrated that PAs induced concentration-dependent increases in micronuclei and G2/M phase cell cycle arrest in three CYP3A variant-expressing TK6 cell lines. Using Western blotting, we observed that PA-induced apoptosis, cell cycle changes, and DNA damage were primarily mediated by CYP3A4. Benchmark dose (BMD) modeling demonstrated that lasiocarpine, of the three PAs, was the most potent inducer of micronuclei, with a BMD100 of 0.036 μM. These results indicate that our TK6 cell system holds promise for genotoxicity screening of compounds requiring metabolic activation, identifying specific CYPs involved in bioactivation, and discriminating the genotoxic compounds that have different chemical structures. Graphical abstract: Image 1 Highlights: A battery of 14 CYP-expressing TK6 cell lines were created for genotoxicity testing. Pyrrolizidine alkaloid (PA)-induced genotoxicity was investigated in these metabolically competent TK6 cell lines. Genotoxicity of lasiocarpine, riddelliine, and senkirkine was mainly catalyzed by CYP3A4. To a lesser extent, CYP3A5 and 3A7 were also involved in PA bioactivation. Lasiocarpine has the highest genotoxic potency, followed by riddelliine and senkirkine.